2022
DOI: 10.1002/ps.6808
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of multiple overexpressed carboxylesterase genes to indoxacarb resistance in Spodoptera litura

Abstract: BACKGROUND As an important family of detoxification enzymes, carboxylesterases (CarEs) have important roles in the development of insecticide resistance in almost all agricultural pests. Previous studies have suggested that enhancement of CarE activity is an important mechanism mediating indoxacarb resistance in Spodoptera litura, and several CarE genes have been found to be overexpressed in indoxacarb‐resistant strains. However, the functions of these CarE genes in indoxacarb resistance needs to be further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Indoxacarb is a potent novel insecticide for crop protection because to its safety for humans and non-target organisms, superior environmental and residual qualities, broad spectrum, and quick reduction in insect feeding [ 24 ]. However, numerous studies have indicated that a number of insects have recently evolved resistance to indoxacarb due to its widespread use, including S. litura [ 29 ], such as C. rosaceana [ 30 ], M. domestica [ 31 ], S. exigua [ 32 ], P. xylostella [ 33 ] and H. armigera [ 34 ] have developed a significant level of resistance. Furthermore, resistance to several Bt maize products expressing Cry1F and Cry1Ab proteins has been reported in the field, increasing the use of chemical insecticides against S. frugiperda in maize [ 13 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indoxacarb is a potent novel insecticide for crop protection because to its safety for humans and non-target organisms, superior environmental and residual qualities, broad spectrum, and quick reduction in insect feeding [ 24 ]. However, numerous studies have indicated that a number of insects have recently evolved resistance to indoxacarb due to its widespread use, including S. litura [ 29 ], such as C. rosaceana [ 30 ], M. domestica [ 31 ], S. exigua [ 32 ], P. xylostella [ 33 ] and H. armigera [ 34 ] have developed a significant level of resistance. Furthermore, resistance to several Bt maize products expressing Cry1F and Cry1Ab proteins has been reported in the field, increasing the use of chemical insecticides against S. frugiperda in maize [ 13 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its function in interplant communication, the specific role of MeJA in insect defense responses is poorly understood. The tobacco cutworm, Spodoptera litura (Fabricius), is a major widespread and broadly polyphagous pest that feeds on a variety of important economic crops, such as tomato, cotton, soybean, tobacco, and peanut [ 44 ]. In this study, we analyzed the growth of S. litura and its detoxification ability against xanthotoxin after exposure to different concentrations of MeJA fumigation, and the effective role of MeJA in inducing insects’ defense responses to the toxin was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression and mutation are two major mechanisms for CarE-mediated insecticide resistance through enhanced detoxification of insecticides, , which has been widely reported in Myzus persicae, Culex mosquitoes, Drosophila melanogaster, Bemisia tabaci, Aphis gossypii, Lucilia cuprina, Nilaparvata lugens, Tetranychus urticae, P. xylostella, and Spodoptera litura . Generally, there are two ways for CarEs to contribute to insecticide metabolism; one is to delay or prevent the interaction between insecticides and the target site through sequestration, and the other is the enhanced metabolism of the insecticides. , Although CarE-mediated insecticide resistance and the underlying mechanisms have been extensively investigated, the roles of CarEs in detoxification of multiple insecticides are rarely reported.…”
Section: Introductionmentioning
confidence: 99%